Optimalisasi Pemasaran BUMDes “Lestari Jaya” dan UMKM Desa Sanggung Gatak Sukoharjo untuk Meningkatkan Omzet di Masa Pandemi - Suranta, Sri; Widagdo, Ari Kuncara; Zoraifi, Renata; Sulardi, Sulardi (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this service activity is to increase the business development of Village Owned Enterprises (BUMDes) and Micro Small and Medium Enterprises (MSMEs) through service delivery or delivery of new BUMDes products and the use of appropriate marketing methods. with BUMDes and MSMEs. PKM activities are focused on developing BUMDes businesses and implementing BUMDes marketing methods both with conventional methods and through the internet. The service methods carried out are: (1) a preliminary survey to obtain data and information to find out the root of the problem, and (2) provide solutions to problems by conducting marketing training. The result achieved is that the management of BUMDes and MSMEs can increase their marketing competence, both conventional marketing and internet-based marketing. The conclusion is that marketing training is carried out to improve the marketing competence of both BUMDEs and MSME managers so that they can increase sales turnover.